A Reporting Compliance of National Fisheries Authority of Papua New Guinea - Brown, Alistair (Pergamon, 2015)
Through textual analysis, this paper takes into account documentary evidence of the Auditor-General׳s audit commentaries of the reporting compliance of the National Fisheries Authority of Papua New Guinea for the period 2006–2012. The results of the analysis show that the National Fisheries Authority׳s financial statements are late, unprepared or qualified. The study suggests ways the authority might improve its reporting compliance at relatively little cost, and how using national reporting compliance instruments may enhance national fisheries policy. The findings are of critical importance for fishing authority local managers, policy-makers and practitioners interested in providing compliant financial and operational reporting to meet the decision needs of its key stakeholders.